Smart grid and power quality issues - Rini Ann Jerin, Amalorpavaraj; Prabaharan, Natarajan; Nallapaneni, Manoj Kumar; Kaliannan, Palanisamy; Subramaniam, Umashankar (Elsevier, 2018)
The future electricity grid requires smart features like flexible, accessible, reliable, and quality power supply. These features are effectively offered by the smart grid system. The components of the smart grid include renewable sources and controllable loads. Due to the controllable feature of the load, various changes occur with respect to the voltage values and harmonics. Therefore, power quality (PQ) issues with respect to smart grids become a major topic is explained. This chapter includes the PQ issues and its effects in AC microgrids and DC microgrids. The PQ concerns with respect to voltage variations, transients, and harmonics are discussed. The PQ issues due to the demand side management schemes are discussed. Also, the future trends in introducing new PQ indices are discussed in this chapter.